The impact of zakat distribution on social welfare a case study of Selangor zakat agencies, Malaysia - Ashurov, Sharofiddin; Othman, Anwar Hasan Abdullah; Syed Jaafar Alhabshi, Syed Musa (IIUM Press, 2019)
This study empirically examines the effectiveness of yearly zakāt distribution as an instrument for social welfare in the state of Selangor, Malaysia. The study applied the autoregressive distributed lag (ARDL) approach to examine these relationships over the period from 2010 to 2018. Overall, the study found that the zakāt distribution contributes significantly to social welfare through education at a significance level of 5% and contributes inadequately through income level at 10% level of significance. This indicates that the current zakāt distribution system in Selangor provides only a marginal influence on increasing the income of the poor. Furthermore, the zakāt distribution was statistically insignificant to social welfare through healthcare. These findings suggest that the current distribution channels of health are insufficient to improve social welfare and should be improved by offering social health insurance policy for zakāt beneficiaries. This can be done via ratification insurance plan between zakāt agencies and insurance companies to cover the basic health needs for zakāt recipients.